Policy perspectives on OTC derivatives market infrastructure - Darrell Duffie; Ada Li; Theo Lubke (Federal Reserve Bank of New York, 2010)
In the wake of the recent financial crisis, over-the-counter (OTC) derivatives have been blamed for increasing systemic risk. Although OTC derivatives were not a central cause of the crisis, the complexity and limited transparency of the market reinforced the potential for excessive risk-taking, as regulators did not have a clear view into how OTC derivatives were being used. We discuss how the New York Fed and other regulators could improve weaknesses in the OTC derivatives market through stronger oversight and better regulatory incentives for infrastructure improvements to reduce counterparty credit risk and bolster market liquidity, efficiency, and transparency. Used responsibly with these reforms, over-the-counter derivatives can provide important risk management and liquidity benefits to the financial system.
Keywords: E61; G01; G10; G18; 330; OTC derivatives; central counterparty; centralized data repository; collateral management; electronic trading platform; exchange; market transparency; regulation; systemic risk